The Implementation of Policy the Index of Norms, Standards, Procedures and Criteria for State Civil Apparatus Management at the Regional Office XI of the Manado National Civil Service Agency - Sandag, Marie Agustina; Bida, Obed; Pangemanan, Fanley; Mustaking, Mustaking (Jurnal Pemerintahan dan Politik Lokal, 2025)
This study aims to analyze and identify the implementation of the ASN Management NSPK Index policy, its supporting and inhibiting factors, and efforts made to overcome obstacles. This study design uses a qualitative descriptive approach with data collection techniques through observation, questionnaires, and documentation. The results of the study indicate that the implementation of the ASN Management NSPK Index policy at the BKN Manado Regional Office XI has not been optimal, especially in terms of communication, resources, and bureaucratic structure, although the disposition indicators have been running well. The main obstacles include inconsistent communication, limited frequency of socialization, limited number of ASN Management Auditors, and fragmentation between work units in regional agencies that hinder policy implementation. To overcome these obstacles, online socialization, mentoring by ASN Management Auditors, and provision of guidebooks and assessment matrices have been carried out. Based on the results of the study, it can be concluded that the implementation of the policy has been running well, although there are still obstacles in communication, resources and bureaucratic structure.